Insight on Stock Market Using Data Mining (European Journal of Engineering Science and Technology, 2019)
A stock market is the aggregation of buyers and sellers of stocks, which represent ownership claims on businesses. Rise and Fall of stock prices are affected by many factors like Government policies, Institutional Buyers, Retail Buyers and many more. There are many algorithms that help investors to have a better insight into the stock market. We use the three best algorithms and get an average of it. We then show that we have achieved the maximum accuracy possible.